Pengaruh Model Pembelajaran Team Games Tournament Terhadap Minat Belajar Pada Mapel IPAS Kelas 5 - Anggraini, Chofifa; Choirin Attalina, Syailin Nichla (Universitas Negeri Makassar, 2024)
The primary issue this study addresses is students' lack of interest in science and science-related subjects. The purpose of this study is to determine how students' interest in learning is impacted by the Teams Game Tournament learning model, both before and after it is used. In this study, a quantitative research methodology was adopted. In this study, a single group pretest-posttest was used to gather data. Based on analysis using sample t test results, the calculated t value is 5.137, which is greater than the t table value for df 12. Conversely, when the sig(2-tailed) value is less than 0.000, Ho is rejected and Ha is accepted. In this sense, it can be concluded that using the Team Games Tournament model has an impact on class V students' interest in learning science subjects.